The Urnfield period Dragomelj I hoard - Turk, Peter (Arheološki vestnik, 2025)
The hoard with over 86 kg of metal products unearthed in the settlement at Dragomelj is dated to Ha B1 and com-plements the remains of foundry activities in the nearby settlement at Podgorica. The twin settlements were centres of collection, production, and exchange located on the transport routes that connected the eastern Alpine copper mines with areas to the south. The products in the hoard include biconical ingots with a shaft hole that show a significant correlation between form and chemical composition, which is characterised by tin alloy and modest trace elements (Sb, Ni, As). In contrast, the biconical ingots without a shaft hole contain higher amounts of trace elements. This suggests that the Bronze Age smiths produced different forms of ingots to distinguish between the different metal compositions. The diverse composition of the ingots also indicates the different origins of the chalcopyrite and polymetallic ores used in the production process. The tin alloy of most biconical and some plano-convex ingots is the result of recycling or intentional addition of tin. The analysis of lead isotopes confirms the diverse origin of the objects. In addition to the probable source areas of Mitterberg and Trentino, the supply of copper ores from the nearby Karavanke Mountains remains a possibility.
Keywords: analize svinčevih izotopov; depo; Dragomelj; hoard; late bronze age; lead-isotope analysis; metallurgy; metalurgija; pozna bronasta doba